2002
DOI: 10.1046/j.1365-246x.2002.01557.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Mongol-Okhotsk Ocean as constrained by new palaeomagnetic data from the Mongol-Okhotsk suture zone, Siberia

Abstract: Summary This paper presents new data from palaeomagnetic investigations on the Upper Palaeozoic and Mesozoic geological units from the Siberian platform and the Mongol–Okhotsk suture zone. Within the southern portion of the Mongol–Okhotsk suture we collected palaeomagnetic samples from the Late Permian Belektuy formation (Borzya region; 50.7°N, 116.9°E) and the Middle–Late Jurassic Shadaron formation (Unda‐Daya; 51.5°N, 117.5°E). We sampled the Late Permian Alentuy formation (Khilok region; 50.8°N, 107.2°E), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
230
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(256 citation statements)
references
References 27 publications
23
230
0
3
Order By: Relevance
“…This means that an abundance of subducted oceanic slabs remained in depth until this time. During late Middle through early Late Jurassic time, the combined North China-Mongolia block collided with the Siberia plate along the Mongol-Okhotsk suture to the north (Zorin et al 1995;Kravchinsky et al 2002). Thus, the eastern segment of CAOB remains confined or under a compressional regime.…”
Section: Osmentioning
confidence: 99%
“…This means that an abundance of subducted oceanic slabs remained in depth until this time. During late Middle through early Late Jurassic time, the combined North China-Mongolia block collided with the Siberia plate along the Mongol-Okhotsk suture to the north (Zorin et al 1995;Kravchinsky et al 2002). Thus, the eastern segment of CAOB remains confined or under a compressional regime.…”
Section: Osmentioning
confidence: 99%
“…Certainly not. Şengör and his co-workes have clearly shown that the Mongol-Okhotsk Ocean did not close until the end of the Jurassic using not only age but also stratigraphic, structural and petrographic data, and their conclusion is corroborated by more recent palaeomagnetic observations (Kravchinsky et al, 2002).…”
Section: Comparative Anatomy Of Mountain Beltsmentioning
confidence: 83%
“…Стабильный структурный ансамбль до-кембрийских каледонских террейнов Северного мегаблока, включающий Тувино-Монгольский ми-кроконтинент, сформировался к концу ордовика. Этот мегаблок осложнен структурой Монголо-Охотского залива Палеопацифика, последователь-но закрывавшегося с запада на восток в позднем палеозое и мезозое с быстрым смыканием берегов в конце юры -начале мела [Şengör, Natal'in, 1996;Zorin, 1999;Kravchinsky et al, 2002]. Герцинские (силлурийско-каменноугольные) островные дуги Южного мегаблока (как части Южномонгольско-Хинганской или Тяньшань-Южнохингалинской зо-ны) отделялись от Северо-Китайского кратона и аккретированных к нему террейнов Солонкерским швом [Yanshin, 1974;Belichenko, Boos, 1990;Tseden et al, 1992;Kozakov et al, 2007;Windley et al, 2007;Parfenov et al, 2003;Wan, 2010].…”
Section: соотношения низкоскоростных аномалий переходного слоя с фрагunclassified